THE INFLUENCE OF HPC-L AND EUDRAGIT L30 D-55 ON DELAYED RELEASE OMEPRAZOLE MAGNESIUM MULTIPLE-UNIT PELLET SYSTEM - Mummidi, Varalakshmi; Rezwana, Shaik (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study is to develop optimum, stable, delayed release pellets of omeprazole magnesium (20.6 mg dose). Omeprazole magnesium is a proton pump inhibitor that suppresses gastric acid secretion by specific inhibition of the H+/K+ -ATPase at the secretory surface of the gastric parietal cell, which is orally administered drug, whereas omeprazole magnesium is degraded in stomach pH, so it is formulated as delayed release dosage form to absorb in intestinal pH. Methods: The formulation of delayed release pellets of omeprazole magnesium was developed by enteric film coating process varying the compositions of drug loading, barrier coating, and enteric coating using fluid bed processor. The prepared multiple pellets were filled into hard gelatin capsules as a single unit dosage forms. Results: The dissolution profile of formulation (F8) contains the efficient amount of hydroxypropyl cellulose-L and Eudragit L30 D55 leads to effective release of drug in 30 min. Fourier transform infrared and differential scanning colorimeter studies were conducted for the optimized formula to prove that the formula was not having incompatibility between the drug and excipients. The scanning electron microscopy studies were conducted to know the surface morphology of the pellets. Conclusion: It was concluded that optimized formulation (F8) shown good similarity with innovator. The results of the accelerated stability of final formulation revealed that storage conditions were excellent.